Intellectual Capital dan Investment Decisions: Peran Mediasi Annual Report Readability pada Badan Usaha Milik Negara di Indonesia - Julita; Desmiyawati; Deby Kurnia; Rio J.M Marpaung; Luthfi iznillah, Muhammad; Sandi Pratama; Pramesti Wisa Zerfi (Akuntansi & Ekonomika, 2025)
This study aims to analyze the effect of Intellectual Capital (IC) on investment decisions with Annual Report Readability (AnRR) as a mediating variable. The study employs a quantitative approach with a research sample consisting of 20 non-financial state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange during the 2018–2023 period. A census sampling technique was applied, and secondary data were obtained from annual reports available through the IDX and the companies’ official websites. Data analysis was carried out using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that IC has a significant effect on investment decisions, highlighting the importance of intellectual asset management in attracting investors. Conversely, AnRR does not have a significant effect on investment decisions, either directly or indirectly, in mediating the relationship between IC and investment decisions. Similarly, ROA and leverage were found to have no significant influence.